How to manifest the fertilizer reduction effect of pro-environmental agricultural technologies? From the perspective of farmers’ perception and behavioral adoption - Kuang, Foyuan; Li, Jiatong; Jin, Jianjun; Liu, Changjin; Qiu, Xin (Frontiers in Sustainable Food Systems, 2024)
The ecological and environmental pollution problem at the source of agriculture cannot be ignored, and the manifestation of the fertilizer reduction effect of pro-environmentally agricultural technologies (PEATs) will help motivate farmers to adopt technology, thereby promoting sustainable agricultural development.From the dual perspectives of farmers' perception and behavior effects, this paper uses 607 survey data of Chinese farmers, and an endogenous switching regression model is employed to identify the influencing factors of farmers' adoption of PEATs and manifest its fertilizer reduction effect.The results of the perception survey show that the farmers' recognition of the fertilizer reduction effect of PEATs is not high, and the technical effect needs to be further demonstrated. Moreover, the estimated results suggest that PEATs can significantly reduce the fertilizer application of farmers. Specifically, if farmers who have adopted PEATs do not adopt them, they will apply more chemical fertilizers, the farmers who have not adopted PEATs will use less chemical fertilizer if